2012
DOI: 10.1177/0306624x12444839
|View full text |Cite
|
Sign up to set email alerts
|

Does Consideration of Psychopathy and Sexual Deviance Add to the Predictive Validity of the Static-99R?

Abstract: The Static-99 is the most commonly used actuarial risk assessment tool for the prediction of sexual recidivism. In addition, the use of psychopathy and sexual deviance has been common in assessing sexual offenders, based on research suggesting that these factors have predictive validity. It has also become common practice to modify risk assessments based on the Static-99/99R because of the presence of psychopathy and indicators of deviant sexual interests, although to date there has been no research validating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…Although it seems to make sense that more high-risk scores indicates a higher level of risk than fewer high-risk scores, researchers have had a difficult time finding measure combinations that are associated with an increase in predictive validity. Although some studies have found improved prediction with multiple measures (Lehmann et al, 2013), most others have not (Boccaccini et al, 2009; Looman, Morphett, & Abracen, 2013; Seto, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although it seems to make sense that more high-risk scores indicates a higher level of risk than fewer high-risk scores, researchers have had a difficult time finding measure combinations that are associated with an increase in predictive validity. Although some studies have found improved prediction with multiple measures (Lehmann et al, 2013), most others have not (Boccaccini et al, 2009; Looman, Morphett, & Abracen, 2013; Seto, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This was, in fact, suspected to be the case in previous investigations using data from the RTC. Specifically, it was found that sexual deviance—operationalized as phallometric test results—surprisingly did not improve the prediction of recidivism above and beyond Static-99R scores in sample of high-risk individuals with sexual offense histories (Looman, Morphett, & Abracen, 2013). Similarly, there may have been restriction of range with regard to PCL-R scores among those in our high-risk sample.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that most evaluators who use the PCL-R also use the Static-99R raises questions about how evaluators integrate scores from these measures, especially when one appears to be a stronger predictor of sexual recidivism than the other. There is no agreed-upon method for integrating scores across multiple measures (Vrieze & Grove, 2010), and research examining the combination of PCL-R and Static-99R scores suggests that PCL-R scores do not contribute to the prediction of future sexual offending once Static-99R scores are taken into account (Looman et al, 2012). Informal attempts at integration, based on clinical judgment, are unlikely facilitate accurate decision making, given the well-known shortcomings of clinical judgment (see Grove & Meehl, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only six studies have examined the possible benefits of combining PCL-R and sexual deviance measure scores for predicting sexual recidivism, and three used phallometric measures that may not be available to many evaluators (G. T. Harris et al, 2003; Looman, Morphett, & Abracen, 2012; Rice & Harris, 1997). The remaining three used item or total scores from other assessment measures as indicators of sexual deviance (Hildebrand, de Ruiter, & de Vogel, 2004; Olver & Wong, 2006; Seto, Harris, Rice, & Barbaree, 2004), including the Screening Scale for Pedophilic Interests (SSPI; Seto & Lalumière, 2001), Violence Risk Scale: Sex Offender Version (VRS:SO; Wong, Olver, Nicholaichuk, & Gordon, 2004), and the Sexual Violence Risk–20 (SVR-20; Boer, Hart, Kropp, & Webster, 1997); however, none of these measures appear to be widely used among evaluators conducting sex offender risk assessments (Jackson & Hess, 2007; Neal & Grisso, 2014).…”
Section: Why Do Evaluators Use the Pcl-r In Sex Offender Risk Assessmmentioning
confidence: 99%